Principles and methods of research - Ariola, Mariano M. (Manila : Rex Book Store, 2006)
This book on Principles and Methods of Research is focused on the principles and methods of research, including writing and reporting a research paper. It also provides graduate and undergraduate students, as research producers, with the basic research and effective technical writing skills to help them understand scientific studies as part of their course requirements and in preparation for their career either in the professional or non-professional world.
Chapter 1 Research perspective 1 -- Chapter 2 The Review of related literature and studies 35 -- Chapter 3 Methods and procedures 42 -- Chapter 4 Sampling design 73 -- Chapter 5 Research instruments 82 -- Chapter 6 Statistics: the language of facts 103 -- Chapter 7 Writing a research report 130 -- Chapter 8 Presenting and communicating a research report 150 -- Chapter 9 Writing a term paper 163 -- Chapter 10 Computer-assisted research 179 -- Bibliography 189 -- Appendices 192 -- Glossary of research terms 249 -- Index 274
Includes index.
Keywords: RESEARCH METHODOLOGY